RE-MOLD: Managing recurring mould after flood - Ariane Segelstein; Françoise Collanges (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Historical buildings impacted by the 2021 floods in Belgium, and churches in particular, took several years to dry. In the meantime, mould developed on the furniture and became a recurring phenomenon in some places, where climate control was not possible and the maintenance limited. The project RE-MOLD, elaborated at KIK-IRPA, was an attempt to design new eco-friendly methods to keep control of recurring mould for non-professional users such as parishioners.